BAHASA INGGRIS - Asrida, Elni (Universitas Mahaputra Muhammad Yamin, 2024)
This research addresses the observed discrepancies among students in the second semester of the English program at UIN Bukittinggi in the academic year 2022/2023. Some students showed low vocabulary proficiency together with low listening proficiency, while others showed high proficiency in both areas. The study aims to investigate the relationship between students' vocabulary mastery and their listening ability. Using a correlational design, the research involved a population of 105 second semester English students at UIN Bukittinggi, using cluster sampling due to the larger population size. Data collection methods included tests to assess vocabulary mastery and listening skills. Pearson Product Moment Correlation Coefficient (r) was used for analysis using SPSS 25. The results showed a significant positive correlation (r = 0.892) between students' vocabulary mastery and listening ability. This correlation falls in the high range (0.70-0.90), indicating a robust relationship between the two variables. Hypothesis testing further supported this correlation, with the calculated rxy (0.892) exceeding the critical value of the r-table (0.344) at ? = 0.05. Therefore, the research accepts the alternative hypothesis (Ha) and rejects the null hypothesis (Ho), confirming the positive correlation between students' vocabulary mastery and listening skills.